Occupational diseases among call center operators needing vocal rehabilitation - Altundaş Hatman, Elif; Torun, Sebahat Dilek (La Medicina del Lavoro, 2022)
Background: Work related diseases (WRDs) and occupational diseases (ODs) greatly affect call center operators (CCOs) who experience demanding work expectations and adverse working conditions in their workplace. The aim of this study was to evaluate the sociodemographic and job characteristics of CCOs diagnosed with OD, and to describe the changes in employment status after diagnosis. Methods: This descriptive study is based on the electronic data records of Istanbul Occupational Diseases Hospital available from February 2007 to March 2018. Results: According to the health board reports, 122 of the 173 (70.5%) CCOs had a confirmed OD diagnosis, 85.2% were females and the mean age was 27.5 years. Vocal cord disorders were the most frequent ODs (64.8%), followed by hearing loss (12.5%), dysphonia (10.2%) and temporomandibular disorders (4.7%). Vocal cord nodules (VCN) were found to be more frequent among females compared to males (92.9% vs 62.4%, p